Efecto de la aplicación del bioabono proveniente de desechos de cervecería en el rendimiento y crecimiento de los cultivos de lechuga (Lactuca sativa) y brócoli (Brassica oleracea Var. Itálica) en la Quinta Experimental Docente “La Argelia”, provincia de Loja. - Correa Peña, Stiwart Rigoberto (2022)
Artisanal beer is one of the most produced and consumed alcoholic beverages in Ecuador, its production requires a variety of steps such as: Cereal malting, grinding, maceration, filtration, cooking, fermentation, maturation, clarification and finally packing. On the other hand, the beer industry generates large amounts of industrial waste that cause pollution problems. However, the research for new alternatives that allow progress in environmental and economic management is one of the current priorities. Indeed, these residues can be a favorable substrate for making organic fertilizers and incorporating them into agricultural crops. Since chemical fertilizers are object of controversy due to the environmental negative effects they produce. The testing procedure was carried out at the Quinta Experimental Docente "La Argelia", of the Faculty of Agricultural Engineering of Universidad Nacional de Loja, located in Loja city with the objective of evaluating the effects of biofertilizer from brewery waste on the yield and growth of crops of lettuce (Lactuca sativa) and broccoli (Brassica oleracea Var. Italica) in the province of Loja, for this purpose a completely randomized design was used with a type of biofertilizer and 4 doses, with 3 repetitions. The results indicated that the application of biofertilizer to the soil in the cultivation of broccoli and lettuce were positive, in the variable height of the plant, the broccoli reached 45,33 cm at 90 days. In the diameter of the pellet, at harvest stage with 15,66 cm. In the weight of the pellet with 434 g, and the highest yield obtained was 0,43kg/treatment. In the case of lettuce, specially at 75 days after the transplant it reached 14,77 cm, in the diameter of the head in the harvest stage with 9,34 cm, in the weight of the head with 458,75 g and the highest yield reached was 0,46 kg/treatment. Of the doses of the biofertilizer evaluated, the dose T3D3 (3 kg/m²) and T2D3 (2 kg/m²) had the greatest effects on the growth and development of the plants as well as on height, diameter and weight, noting the best yields per treatment. Keywords: waste, brewery, effect, broccoli, lettuce, biofertilizer, alternatives, performance.